Ôn tập chương VI

Ryoji

Chứng minh|
a) cos(a+b)cos(a-b) = cos2a - sin2b

b)\(cos\left(\dfrac{\pi}{4}+a\right)cos\left(\dfrac{\pi}{4}-a\right)+\dfrac{1}{2}sin^2a=\dfrac{1}{2}cos^2a\)

Nguyễn Việt Lâm
15 tháng 2 2019 lúc 23:34

Áp dụng công thức biến tích thành tổng:

\(cos\left(a+b\right).cos\left(a-b\right)=\dfrac{1}{2}\left(cos2a+cos2b\right)\)

\(=\dfrac{1}{2}\left(2cos^2a-1+1-2sin^2b\right)=\dfrac{1}{2}\left(2cos^2a-2sin^2b\right)\)

\(=cos^2a-sin^2b\)

\(cos\left(\dfrac{\pi}{4}+a\right).cos\left(\dfrac{\pi}{4}-a\right)+\dfrac{1}{2}sin^2a=\dfrac{1}{2}\left(cos\dfrac{\pi}{2}+cos2a\right)+\dfrac{1}{2}sin^2a\)

\(=\dfrac{1}{2}cos2a+\dfrac{1}{2}sin^2a=\dfrac{1}{2}\left(cos^2a-sin^2a\right)+\dfrac{1}{2}sin^2a\)

\(=\dfrac{1}{2}cos^2a\)

Bình luận (0)

Các câu hỏi tương tự
YếnChiPu
Xem chi tiết
Sách Giáo Khoa
Xem chi tiết
Sách Giáo Khoa
Xem chi tiết
Sách Giáo Khoa
Xem chi tiết
Helios Aiden
Xem chi tiết
Sách Giáo Khoa
Xem chi tiết
Sách Giáo Khoa
Xem chi tiết
Nguyễn Thị Bích Vân
Xem chi tiết
Ryoji
Xem chi tiết